Effect of grain boundary engineering on hydrogen embrittlement in Fe-Mn-C TWIP steel at various strain rates. (September 2018) - Kwon, Young Jin; Seo, Hyun Joo; Kim, Jae Nam; Lee, Chong Soo
Graphical abstract: Highlights: Hydrogen cracking increased with decreasing strain rate. Grain boundary engineering (GBE) promoted special boundaries. GBE provided some suppression of H-cracking at slow strain rates. Abstract: The influence of strain rate (10 −3  ≤  ε ˙  ≤ 10 −5  s −1 ) on hydrogen embrittlement behavior of Fe−17Mn − 0.8C (wt.%) TWIP steel was investigated. Two types of specimens were tested; one (AR) was hot-rolled, and the other (GBE) was further processed by grain boundary engineering. After hydrogen charging, the fracture strength (FS) and ductility of AR samples decreased as ε ˙ decreased, because increasing numbers of H atoms accumulated near crack tips. However, after hydrogen charging, the FS and tensile ductility of GBE samples were not decreased much even at low ε ˙, because special boundaries suppressed hydrogen-induced crack initiation and propagation.